Spy Watching : Intelligence Accountability in the United States. - Johnson, Loch K. (Oxford University Press, 2017)
Given the dangers they face, nations must have effective spy services. Democracies must also ensure, however, that their spies are well supervised in order to prevent abuses of secret power. In Spy Watching, a sweeping history of how America's spy agencies have wrestled with public accountability, one of America's leading experts on the intelligence community, shows how the tension between liberty and security has been at the heart of every major intelligence controversy from the early Cold War up through the issue of Russia's role in the 2016 election.